Językowa materia i sens w poezji Adama Zdrodowskiego - Kujawa, Dawid (Przestrzenie Teorii, 2015)
Polish poetry of the 1990s was shaped primarily by the works of Andrzej Sosnowski, an author who introduced the New York tradition into our language. The poet Adam Zdrodowski, who debuted in 2005, is often referred to as Sosnowski’s most capable student and it is for this reason that literary criticism fails to accord Sosnowski’s poetry the attention it deserves. In this paper I strive to demonstrate that Zdrodowski is first and foremost a student of John Ashbery; it should be noted that the author of Przygody, etc. reads the New York poetry in a very different way to Sosnowski.